Assessing the impact of lake attributes on rental prices - Icka, Engjëllushe (Academica turistica, 2025)
This study aims to quantify the economic value of environmental, structural and locational characteristics that influence rental prices of holiday flats in the Lake Ohrid region of Albania. A hedonic pricing model is applied to a dataset of 164 holiday flats listed on Booking.com, covering weekend stays across the peak tourist season. A partially log–log regression specification is used, with both rental price and flat area log-transformed to account for skewness and diminishing returns. The results highlight the strong effect of natural amenities: lake views and proximity to greenery increase rental prices by approximately 12% and 15%, respectively. Structural features such as larger flat size, greater bed capacity, newer construction, and the inclusion of breakfast services also significantly raise rental prices. In contrast, features like floor level, lift access, parking availability and balconies did not show a significant price effect. The model also reveals that greater distance from the municipal hospital reduces rental price, underscoring the importance of accessibility. These findings offer practical guidance for real estate investors, hospitality providers, and local authorities working to support sustainable tourism and regional development.
Keywords: Albania; Albanija; atributi jezer; hedonic pricing; hedonistična cena; lake attributes; Lake Ohrid; nenadzorno vrednotenje; non-market valuation; Ohridsko jezero